Using Video-Based Instruction via Augmented Reality to Teach Mathematics to Middle School Students With Learning Disabilities. (July 2020) - Kellems, Ryan O.; Eichelberger, Carrie; Cacciatore, Giulia; Jensen, Mikaela; Frazier, Brynn; Simons, Kalee; Zaru, Mai
The purpose of this study was to examine the effectiveness of video-based mathematics instruction for seven middle school students with specific learning disability (SLD), using an augmented reality-based training package. The dependent variable was the percentage of steps students performed correctly to solve each type of mathematics problem. The independent variable was the augmented reality video-based intervention, which used video to model the individual steps for solving four types of multistep mathematics problems: (a) addition and subtraction of integers, (b) multiplication and division of integers, (c) using ratio reasoning to convert measurement units, and (d) using multiplication and division to calculate rate of change. Results indicated a functional relation between the video-based mathematics intervention and the percentage of steps completed correctly for each type of problem. All seven participants showed significant gains immediately after receiving the intervention and maintained improved problem-solving skills in at least three out of the four problem categories.